Higher Expression of Activation-induced Cytidine Deaminase Is Significantly Associated with Merkel Cell Polyomavirus-negative Merkel Cell Carcinomas - Matsushita, Michiko (Yonago Acta Med, 2017)
BACKGROUND: Merkel cell carcinomas (MCCs), clinically aggressive neuroendocrine skin cancers, are divided into Merkel cell polyomavirus (MCPyV)-positive and -negative tumors, which show different clinicopathological features and may develop through different mechanisms of carcinogenesis. Aberrant expression of activation-induced cytidine deaminase (AID) as a genomic modulator was demonstrated through pathogen-related NF-κB signal in Helicobacter pylori-associated gastric cancer, adult T cell leukemia/lymphoma (HTLV-1), hepatoma (HCV), and Burkitt lymphoma (EBV). METHODS: To elucidate the relation of aberrant AID expression in MCPyV-positive and -negative MCCs, we evaluated immunohistochemical expressions of AID and AID-regulating factors between 24 MCPyV-positive and 17 MCPyV-negative MCCs. RESULTS: AID expression was significantly higher in MCPyV-negative MCCs than MCPyV-positive ones (P = 0.026), although expression of NF-κB p65 (phospho S536) (AID-enhancer) was significantly higher in MCPyV-positive MCCs than MCPyV-negative ones (P = 0.034). Expressions of PAX5 and c-Myb were not significantly different between these subgroups. Expressions of AID and AID-regulating factors were not correlated to prognosis of MCC patients. CONCLUSION: Our findings suggest that although pathogen-induced AID expression through upregulation of NF-κB may be relevant to carcinogenesis of MCPyV-positive MCCs, the significantly higher aberrant AID expression in MCPyV-negative MCCs is consistent with the fact that MCPyV-negative MCCs have an extremely higher mutation burden than MCPyV-positive ones.